2001
DOI: 10.1200/jco.2001.19.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Single-Dose Radiation Therapy of Liver Tumors: Results of a Phase I/II Trial

Abstract: Stereotactic single-dose radiation therapy is a feasible method for the treatment of singular inoperable liver metastases with the potential of a high local tumor control rate and low morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
260
1
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(279 citation statements)
references
References 22 publications
8
260
1
10
Order By: Relevance
“…The investigators from Heidelberg observed that local control was more favorable after 26 Gy than after 14 Gy delivered in 1 fraction. 23 The team from Wurzburg found a 2-year local control of 82 vs. 58% after delivering 36-37.5 Gy in 3 fractions or 26 Gy in 1 fraction vs. 30 Gy in 3 fractions. 7 Later on, in the North American multiinstitutional phase I/II study, the dose was escalated from 36 to 60 Gy with reported 2 years local control rate of 92%.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators from Heidelberg observed that local control was more favorable after 26 Gy than after 14 Gy delivered in 1 fraction. 23 The team from Wurzburg found a 2-year local control of 82 vs. 58% after delivering 36-37.5 Gy in 3 fractions or 26 Gy in 1 fraction vs. 30 Gy in 3 fractions. 7 Later on, in the North American multiinstitutional phase I/II study, the dose was escalated from 36 to 60 Gy with reported 2 years local control rate of 92%.…”
Section: Discussionmentioning
confidence: 99%
“…58,59 In conclusion, a prudent approach, is to use dosevolume constraints for organs at risk summarized in updated guidelines 2,54 or determined in high-quality phase I trials. 16 …”
Section: Dose-volume Constraints For Organs At Riskmentioning
confidence: 99%
“…13,18 This illustrates the positive impact that international protocols and recommendations have in our setting. [20][21][22][23][24] An USA national survey from 510 radiation oncologists in 2010 reported that lung followed by spine and liver were the most common sites of SBRT treatment and three fractions were the most common fractionation used. They also reported a fast increase on SBRT application (from less than 10% in 2000 to 65% in 2010) and most of the centers are planning to increase the SBRT applications.…”
Section: Resultsmentioning
confidence: 99%